Employee Orientation, Training, and Development in improvements of Employee Performance at University in Surabaya - Tubagus Purworusmiardi; Hary Adi Laksono; Elok Damayanti; Amrun Rosyid (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This study aims to determine the effect of employee orientation, training, and development on the performance of university employees in the city of Surabaya. Design/methodology/approach: The research uses an explanatory quantitative approach. The population in this study were all Universities in Surabaya, amounting to 84 units. Sampling technique with total sampling. Data collection is done using google Forms. The data collected were analyzed using multiple linear regression analysis, t-test, and F test. Findings: Factors of employee orientation, training and development individually influence the performance of University employees in Surabaya. The results of the study state that work development have a dominant influence on the performance of university employees in Surabaya Paper type: Research paper